Spatial and Temporal of Meroplankton in a Semi-enclosed Bay: Insights from Ambon Bay - Ruli, Fismatman; Likumahua, Sem; Salamena, Gerry Giliant; Romdon, Ahmad (Bogor Agricultural University, Indonesia, 2026)
Meroplankton is a temporary planktonic phase of marine organisms. Despite their critical role in the ecosystem, the study of their distribution and dynamics in Ambon Bay is still limited. Therefore, this study aims to investigate the spatial distribution and dynamics of meroplankton in Ambon Bay. Study conducted during the southeast monsoon (August and September) to transition II (October and November) 2022. Meroplankton was captured using a plankton net towed vertically from approximately 20 m, near the bottom, to the surface, and immediately preserved in formaldehyde (final concentration of 4%). A stemple pipette was used for subsamples, and they were observed under a stereo microscope. Thirteen groups of meroplankton were recorded, with three groups (Bryozoa, Phoronida, and Brachiopoda larvae) being newly reported in this area. Bivalvia and Polychaeta larvae had the highest abundance. Meroplankton abundance was consistently higher in the inner Ambon Bay (240.62-3029.02 ind.m-3) than in the outer Ambon Bay (85.63-955.41 ind.m-3), highlighting the ecological significance of this area as a potential spawning and larval nursery ground. Most meroplankton taxa were recorded across all sampling seasons, except for Phoronida and Stomatopoda, which were only observed during the southeast monsoon. In comparison to previous studies, the abundance of Echinodermata peaked during the transition I to the southeast monsoon, whereas Polychaeta exhibited peak abundance during the northwest monsoon. This study offers significant insights into the diversity, spatial distribution, and dynamics of meroplankton in Ambon Bay.